CELSR2 deficiency suppresses lipid accumulation in hepatocyte by impairing the UPR and elevating ROS level. Issue 10 (3rd September 2021) - Tan, Junyang; Che, Yaping; Liu, Yanyan; Hu, Jiaqiao; Wang, Wenjun; Hu, Liubing; Zhou, Qinghua; Wang, Hao; Li, Jianshuang
Abstract: Cadherin EGF LAG seven‐pass G‐type receptor 2 (CELSR2), a mammalian orthologue of drosophila flamingo, belongs to the cadherin subfamily. CELSR2 mainly function in neural development and cilium polarity. Recent studies showed that the CELSR2 gene is related to many human diseases, including coronary artery disease, idiopathic scoliosis, and cancer. Genome‐Wide Association Studies data showed that SNP in the CELSR2‐PSRC1‐SORT1 gene loci has a strong association with circulating lipid levels and coronary artery disease. However, the function and underlying mechanism of CELSR2 in hepatic lipid metabolism remain unknown. Here, we found that CELSR2 expression is decreased in the liver of NAFLD/NASH patients and db/db mice. Depletion of CELSR2 significantly decreased the lipid accumulation in hepatocytes by suppressing the expression of lipid synthesis enzymes. Moreover, CELSR2 deficiency impaired the physiological unfolded protein response (UPR), which damages the ER homeostasis, and elevates the reactive oxygen species (ROS) level by decreasing the antioxidant expression. Scavenging of ROS by N‐acetylcysteine treatment could restore the decreased lipid accumulation of CELSR2 knockdown cells. Furthermore, CELSR2 loss impaired cell survival by suppressing cell proliferation and promoting apoptosis. Our results uncovered a new role of CELSR2 in regulating lipid homeostasis and UPR, suggesting CELSR2 may be a new therapeutic target for non‐alcoholic fatty liver disease.